The Teachers’ Perception on the Use of Cooperative Learning Model for Improving Learners’ Reading Fluency - Asih Sari Ningrum; irwandi irwandi (Journal of English Language and Education, 2021)
The learners’ reading fluency becomes one of the crucial problems in teaching reading. The preliminary research indicates that the students find the obstacles in understanding the structure of the sentence in reading text quickly. It is also difficult for them to understand the meaning of word in the text. To overcome these problems, the teachers have applied the use of cooperative learning model. The design of this research is descriptive qualitative. The questionnaire is used to collect the data. In addition, for the technique of data collection, the researcher used questionnaire which the researcher gave that questionnaire to the English teachers. The researcher analyzed the answers of the English teachers by using steps of qualitative data analysis. The results show that the teachers agree with the application of the cooperative learning model. The form of the teachers’ view is marked by their agreeing on the cooperative learning model.